Comparación in vitro del aceite esencial de cáscara de limón y el aceite esencial de cáscara de naranja como solventes de gutapercha de uso endodóntico - Ramírez Espinoza, Mónica Lucía (2017)
The purpose of the current investigation was to test the in vitro effectiveness of the essential oil of lemon rind and essential oil of orange rind as gutta-percha solvents of endodontic use. The research is basic, experimental and explanatory. It was carried out in a sample of 44 cones of gutta-percha of second series n°80 (Dentsply, Maillefer, Switzerland), standardized according to the norm ISO 6877, and with expiry date until 2017. The results showed a statistically significant high variation to dissolve the gutta-percha by using the essential oil of lemon rind within in comparison to the essential oil of orange rind (p<0,05), thus demonstrating that the essential oil of lemon rind is more effective Than the essential oil of orange rind.